Pengaruh Person Job-Fit dan Job Burnout terhadap Kepuasan Kerja Gen Z (Studi Pada Pengikut Akun Twitter Worksfess) - Yulianto, Wahyu; Nusannas, Iman Sidik; Safinatunnajah, Salma (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This research was conducted to find out how the influence of Person Job Fit and Job Burnout variables on Gen Z Job Satisfaction. In this study, Person Job Fit and Job Burnout variables were independent variables and job satisfaction was the dependent variable. Primary data collection using simple random sampling technique as a sample, with a total of 80 gen z respondents as followers of the Worksfess Twitter account who had resigned. The data analysis method used in this study is multiple linear regression with the help of data processing using SPSS software. Based on the results of the research that has been done, it shows that simultaneously the independent variables have a positive and significant influence on the dependent variable (job satisfaction). And the value of r square shows the number 68.1% which means that all independent variables have a simultaneous effect of 68.1%. Keywords: Person Job Fit, Job Burnout, and Job Satisfaction